작업치료사의 임상 경력에 따른 작업치료직무 중요도에 관한 조사 - 박규용; Ky-uyong Park; 김민호; Min-ho Kim (Journal of the Korean Society of Integrative Medicine, 2021)
Purpose : This study examined the differences in occupational therapists’ jobs depending on their past clinical careers using a survey of the importance of occupational therapy tasks in South Korea. This survey sought to provide fundamental data for strengthening occupational therapists’ capacities and developing clinical training programs for therapists’ future careers. Methods : An online survey was used to collect data from 93 South Korean occupational therapists. The subjects were divided into three groups for the analysis of the importance of occupational therapy tasks, depending on the length of their clinical careers: less than 3 years, from 4 to 6 years, and over 7 years. Results : A within-groups comparison of task importance found that “occupational therapy evaluation” was most important in all three groups. In between-groups comparisons, “patient information check”, “assessment planning and establishment”, “sensory function assessment”, “social skills assessment”, “developmental function improvement”, “basic daily activities training”, “social skills improvement”, and “patient education” demonstrated statistically significant differences (p<.05). Each group showed different priorities. In the less-than-3-years group, “understanding of patient’s needs” was most important, followed by “arm function improvement”, “arm function assessment”, “nerve, musculoskeletal, and motor-related functional improvement”, and “basic daily activities training”. In the 4-to-6-years group, “arm function assessment” was most important, followed by “basic daily activities assessment”, “patient’s needs”, “arm function improvement”, and “patient information check”. In the over-7-years group, “understanding of patient's needs” was most important, followed by “patient information check”, “basic daily activities assessment”, “basic daily activities training”, and “sensory function assessment”. Conclusion : This study found that what occupational therapists consider important in their jobs varies according to their past clinical career and that occupational therapists with more than 7 years’ experience are more aware of the importance of diverse fields of occupational therapy. Differentiated education that considers length of career and a range of training programs for more experienced occupational therapists will be needed in the future.